Application of Microsatellite Loci for Molecular Identification of Elite Genotypes, Analysis of Clonality, and Genetic Diversity in Aspen Populus tremula L. (Salicaceae). (28th December 2015) - Politov, Dmitry V.; Belokon, Maryana M.; Belokon, Yuri S.; Polyakova, Tatyana A.; Shatokhina, Anna V.; Mudrik, Elena A.; Azarova, Anna B.; Filippov, Mikhail V.; Shestibratov, Konstantin A.
Abstract : Testing systems for molecular identification of micropropagated elite aspen ( Populus tremula L.) genotypes were developed on the base on microsatellite (SSR) loci. Out of 33 tested microsatellite loci, 14 were selected due to sustainable PCR amplification and substantial variability in elite clones of aspen aimed for establishment of fast-rotated forest plantations. All eight tested clones had different multilocus genotypes. Among 114 trees from three reference native stands located near the established plantations, 80 haplotypes were identified while some repeated genotypes were attributed to natural clones which appeared as a result of sprouting. The selected set of SSR markers showed reliable individual identification with low probability of appearance of identical aspen genotypes (a minimum of4.8 · 10 - 10 and 1 × 10 −4 for unrelated and related individuals, resp.). Case studies demonstrating practical applications of the test system are described including analysis of clonal structure and levels of genetic diversity in three natural aspen stands growing in the regions where plantations made of elite clones were established.